Fiber optic installation - Johnson, Larry (IEEE, 2009)
Dense Wavelength Division Multiplexing (DWDM) is a photonic technology that is able to increase the number of wavelengths in the same fiber, thus achieving higher aggregate bandwidth that exceeds 1 Tbit/s. Currently, WDM technology is considered the only optical communications technology for the present and future to be deployed in access as well as long-haul and ultra-long haul applications and in various network topologies. WDM is made possible by new photonic technology that brought to bear new photonic components. Among them are optical filters, modulators, gratings, optical amplifiers, couplers, splitters, optical add-drop multiplexers (OADM), optical cross-connects, tunable lasers, superfast and sensitive photodetectors, optical switches, polarizers, compensators and equalizers, and new improved fiber This tutorial identifies the photonic phenomena that determine the bounds of photonic transmission and countermeasure strategies, DWDM principles, optical components, systems and networks